2018
DOI: 10.1002/chem.201803347
|View full text |Cite
|
Sign up to set email alerts
|

Direct Transformation of Arylamines to Aryl Halides via Sodium Nitrite and N‐Halosuccinimide

Abstract: A one-pot universal approach for transforming arylamines to aryl halides via reaction with sodium nitrite (NaNO ) and N-halosuccinimide (NXS) in DMF at room temperature under metal- and acid-free condition is described. This new protocol that is complementary to the Sandmeyer reaction, is suggested to involve the in situ generation of nitryl halide induce nitrosylation of aryl amine to form the diazo intermediate which is halogenated to furnish the aryl halide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 59 publications
2
18
0
Order By: Relevance
“…1 H NMR (500 MHz, CDCl 3 ): δ =7.46 (d, J =5.3 Hz, 1 H), 7.09 (d, J =5.3 Hz, 1 H), 3.90 (s, 3 H) ppm; 13 C NMR (126 MHz, CDCl 3 ): δ =160.5, 131.5, 132.2, 124.2, 117.2, 51.5 ppm. Physical and spectroscopic data were in agreement with those reported in the literature …”
Section: Methodssupporting
confidence: 90%
“…1 H NMR (500 MHz, CDCl 3 ): δ =7.46 (d, J =5.3 Hz, 1 H), 7.09 (d, J =5.3 Hz, 1 H), 3.90 (s, 3 H) ppm; 13 C NMR (126 MHz, CDCl 3 ): δ =160.5, 131.5, 132.2, 124.2, 117.2, 51.5 ppm. Physical and spectroscopic data were in agreement with those reported in the literature …”
Section: Methodssupporting
confidence: 90%
“…Ethyl 3-chlorobenzoate 8b [ 36 ]. The reaction of ethanol 7b (7 mg, 0.150 mmol) according to the general procedure afforded 13 mg (47%) of product 8b , isolated as a colorless oil; IR (neat) cm −1 : 2924, 1727, 1573, 1466, 1370, 1293, 1281, 1256, 915, and 749; 1 H NMR (500 MHz, CDCl 3 ): δ 8.03 (s, 1H), 7.94 (d, J = 7.5 Hz, 1H), 7.56–7.52 (m, 1H), 7.39 (t, J = 7.5 Hz, 1H), 4.39 (q, J = 7.0 Hz, 2H), and 1.41 (t, J = 7.0 Hz, 3H); HRMS (APCI-positive): calcd for C 9 H 10 ClO 2 ([M + H]) + : 185.0369, found: 185.0389.…”
Section: Methodsmentioning
confidence: 99%
“…Batra et al demonstrated that anilines are converted to the respective haloarenes in the presence of N-halosuccinimides and excess amount of NaNO 2 via a diazonium salt intermediate in DMF (iv). [18] Control experiments revealed that this halogenation is actually mediated by a NO 2 X species. Mo et al used electrochemistry to promote halogenations of diazonium salts with NBS, CH 2 I 2 , or LiCl (v).…”
Section: Introductionmentioning
confidence: 99%